2000
DOI: 10.1177/08943180022107645
|View full text |Cite
|
Sign up to set email alerts
|

A Nursing Theory of Personal System Empathy: Interpreting a Conceptualization of Empathy in King’s Interacting Systems

Abstract: This article presents a theory of empathy discovered through rational hermeneutic interpretation within King's personal system. Personal system concepts from King's general systems framework include perception, self, growth and development, body image, space, time, and learning. Propositions for each concept in the personal system were explicated and a theory of nursing empathy was developed. This nursing theory proposes that empathy organizes perceptions; facilitates awareness of self and others; increases se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 30 publications
(33 reference statements)
0
19
0
6
Order By: Relevance
“…According to this model, in the first stage, the nurse has spontaneous and reflexive responses; however, in the second stage, the responses are learned and therefore can be controlled. This model is similar to basic and trained classifications (Alligood & May, 2000). Olsen (2001) defined a three-stage hierarchical developmental structure to explain how nurses understand a patients' personhood and for advanced empathic practice recommended in cognitive structural theory.…”
Section: Related Literature On Empathymentioning
confidence: 99%
“…According to this model, in the first stage, the nurse has spontaneous and reflexive responses; however, in the second stage, the responses are learned and therefore can be controlled. This model is similar to basic and trained classifications (Alligood & May, 2000). Olsen (2001) defined a three-stage hierarchical developmental structure to explain how nurses understand a patients' personhood and for advanced empathic practice recommended in cognitive structural theory.…”
Section: Related Literature On Empathymentioning
confidence: 99%
“…It is an important component of the relationship between staff and service users, and is crucial to ensuring the delivery of quality care (Yu & Kirk, 2009). Research indicates that empathy is vulnerable to erosion by factors including cultural and environmental influences (Alligood & May, 2000). In a longitudinal study with first-year nursing students, Ward, Cody, Schaal, and Hojat (2012) found a significant decline in empathy for participants who had a greater exposure to client interaction.…”
Section: Empathy In Forensic Mental Health Servicesmentioning
confidence: 99%
“…Some examples include gender, interpersonal style, culture, environment, and personality (Alligood & May, 2000). In particular, burnout has been associated in the nursing and medical literature with empathy (Ferri, Guerra, Marcheselli, Cunico, & Di-Lorenzo, 2015) and will be examined in the current study.…”
Section: Burnout: the Potential Influence On Empathymentioning
confidence: 99%
“…Las teorías y modelos referenciadas en este artículo tienen en común el concepto de comunicación como un proceso recíproco que se da entre la enfermera y el persona en las situaciones de encuentro por las que se comunican pensamientos, sentimientos y actitudes; como una experiencia de encuentro o desencuentro; un asunto dinámico que influye y afecta profundamente el grado de cercanía en las situaciones de enfermería; un instrumento que puede inducir cambios en la persona cuidada (39). La comunicación se expresa verbal y no verbalmente durante la interacción, la cual es percibida e interpretada según los contextos propios de los participantes en esta interacción.…”
Section: Resultados Y Discusiónunclassified